Flash Card Media to Improve Qur'an Literacy at Masjid Jami' Nurul Jannah Grobogan in the Era of Posth Truth - Setyaningrum, Vidhy Andika; Alifta, Zeni; Masuwd, Mowafg; Khakim, Ahmad Maulidin Nuril; Putri, Amanda Alifia (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2024)
The Qur'an is a guideline for Muslims in their behavior. But at this time children's Qur'anic literacy is still low. Even though it is known that the age of children is a golden age in the developmental stage, so proper treatment is needed in learning. The purpose of this study is to describe the use of Flash Card Media to Improve Qur'an Literacy in Masjid Jami' Nurul Jannah Grobogan in the Era of posh truth. This research is qualitative research with case study deception. The data collection techniques used in this study were observation of socio-cultural conditions and learning processes in Majsi Nurul Jannah Grobogan, documentation of official mosque documents and interviews with 4 ustadz/uztadzah, 10 students and guardians of students, and community leaders. Data analysis is carried out by sorting, grouping, looking for themes that match the topic of discussion for interpretation. The results showed that flash card media can be used to improve the learning process of the Qur'an which will have an impact on the high literacy of the Qur'an students. This can be seen from the creation of effective and efficient learning systematics applied at the Jami' Nurul Jannah mosque using flash card media. The importance of increasing Qur'an literacy through increasing Qur'an learning using flash card media is the internalization of the Qur'an in the souls of students. So that with this, students will continue to grow and develop with the Qur'an as a guideline and make students have a good religious spirit.